Partial molecular and biological characterization of grapevine leafroll-associated virus 2 isolates from Argentina - Lanza Volpe, Melisa; Moyano, Sabrina Noé; Lijavetzky, Diego; Gomez Talquenca, Gonzalo (2017)
Grapevine leafroll is one of the most important viral disease affecting grapevines the world over. One of the viruses associated with this disease is Grapevine leafroll associated virus 2 (GLRaV-2), which has two remarkable properties: high genetic variability (up to date at least 6 different lineages have been reported) and the unique ability among leafroll-associated viral species to be transmitted by sap inoculation to herbaceous hosts, specifically to Nicotiana spp. The presence of this virus in Mendoza (Argentina), has previously been reported but no information is available relative to the genetic variability of GLRaV-2 isolates of and their biological behavior. The molecular characterization of the CP-p19-p24 genes of the local isolates disclosed that they belong to four of the six described GLRaV-2 lineages. Using at least one isolate of each lineage, mechanical transmission to herbaceous host of the Nicotiana genus were made. Results showed a differential behavior in some combinations isolate/Nicotiana spp. and an incompatible interaction between GLRaV-2 and two new experimental hosts, N. rustica and N. tabacum cv. Samsun and White Burley.